A Study of Impact Response and Its Numerical Study of Hybrid Polypropylene Fiber-Reinforced Concrete with Different Sizes. (8th October 2020) - Liang, Ninghui; Yan, Ru; Liu, Xinrong; Yang, Peng; Zhong, Zuliang
Abstract : Compressive properties of hybrid polypropylene fiber-reinforced concrete (HPFRC) with different sizes of polypropylene fibers (PPFs) under the impact load (10 1 ∼10 2 /s) were tested by using a 74 mm diameter various cross-section split-Hopkinson pressure bar (SHPB), in which the fiber content of fine PPFs was 0.9 kg/m 3 and that of coarse PPFs was 6.0 kg/m 3 . The effect of strain rate and PPF hybridization on the impact characteristics of HPFRC was analyzed. It is found that dynamic compressive properties, including dynamic compressive strength, dynamic compressive strength increase factor (DCF), ultimate strain, and impact toughness, increased with the increase of strain rate. Meanwhile, both fine PPFs and coarse PPFs can enhance the impact strength of concrete, and an appropriate hybridization of two sizes of PPFs in concrete was more effective than the concrete reinforced with one size of PPF. Moreover, a modified constitutive model for HPFRC was proposed based on the Holmquist–Johnson–Cook (HJC) constitutive model. Then, the numerical study of SHPB tests for HPFRC was conducted based on the modified model, which showed that the modified HJC constitutive model could well describe the dynamic stress-strain relationship of HPFRC.